Critical analysis of Shariah screening norms and practices - Htay, Sheila Nu Nu; Abedeen, Zafar; Syed, Ahmed Salman (2013)
Shariah screening is a relatively new phenomenon to the Islamic finance. Until the 1970s, Muslim community generally was reluctant to involve in stock market due to the outright Shariah prohibition, imposed on capital market. In 1990s, a major breakthrough took place in religious ruling pertaining to equity investment and Muslims were allowed to partake in stock market with certain conditions. To ensure that the Shariah portfolio is in harmony with those conditions Shariah screening process is carried out. Since Shariah screening is executed by different Shariah index providers and all providers are bound with the stipulations laid down by the respective Shariah supervisory body there seems to be inconsistency in terms of Shariah screening norms and practice throughout the world. Along with the absence of standardized practice eventually is deemed to hamper the progress of Islamic equity market and it may lower the confidence of investors in the future. Therefore, this research is aimed to investigate the existing differences among the leading Shariah indices and to critically analyze the current Shariah screening norms. The researchers believe that the findings of the study will contribute to the enhancement of Shariah screening practice and will foster the sustainable growth of Islamic equity market.